Do poor and good performing companies report differently? The readability and impression management in corporate narrative documents: Evidence from Northern Europe - Oleh Pasko; Stanislaw Minta; Serhii Rudenko; Mykola Hordiyenko (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
The purpose of this paper is to assess the effect of financial performance on textual features of the CEO's statement. Specifically, given the incentives of poorly performed companies engage in impression management, the study investigates whether companies' reporting strategy hinges on its financial performance. The research questions are tested through analysis of a variety of textual features in the CEO's statement of 30 good and 30 poor performed companies listed on NASDAQ OMX Stockholm. We apply a range of textual characteristics drawn mostly from prior studies in given realm to the specific research of impression management in the CEO's report. Overall our findings do not corroborate impression management claim, as six out of seven our results run counter to assertions made by impression management research. We found although evidence that poorly performed companies more focused on future compared with good performed companies. Finally, we conclude by discussing our results and outlining some avenues for further research.
Keywords: M14; M40; M41; G34; 650; readability; obfuscation; annual reports; CEO’ s statement; accounting narratives; impression management